2018 WSGC Collegiate Rocketry Competition - Tollison, Chandler R (Proceedings of the Wisconsin Space Conference, 2019)
The Wisconsin Space Grant Consortium hosts the Collegiate Rocket Launch Competition every year. The goal of the competition this year was to design and build a rocket to fly to 3000 ft and take a 360Â° photo upon landing. The rocket, Focal Point, used a single external camera that would rotate to achieve a panoramic video. After recovery, the video was stitched into a panoramic photo. Despite several unforeseen challenges on the day of the launch, Focal Point achieved three flights. To reduce weight and achieve an altitude closer to the goal of 3000 ft, six inches of body tube was removed for the final flight. This drastically improved our flight performance. Pioneer Rocketry is very proud to be able to win third place in this competition